Neoadjuvant relatlimab and nivolumab in resectable melanoma - Amaria, Rodabe N.; Postow, Michael; Burton, Elizabeth M.; Tetzlaff, Michael T.; Ross, Merrick I.; Torres-Cabala, Carlos; Glitza, Isabella C.; Duan, Fei; Milton, Denái R.; Busam, Klaus; Simpson, Lauren; McQuade, Jennifer L.; et al. (Nature (London), 2022)
Relatlimab and nivolumab combination immunotherapy improves progression-free survival over nivolumab monotherapy in patients with unresectable advanced melanoma 1 . We investigated this regimen in patients with resectable clinical stage III or oligometastatic stage IV melanoma (NCT02519322). Patients received two neoadjuvant doses (nivolumab 480 mg and relatlimab 160 mg intravenously every 4 weeks) followed by surgery, and then ten doses of adjuvant combination therapy. The primary end point was pathologic complete response (pCR) rate 2 . The combination resulted in 57% pCR rate and 70% overall pathologic response rate among 30 patients treated. The radiographic response rate using Response Evaluation Criteria in Solid Tumors 1.1 was 57%. No grade 3–4 immune-related adverse events were observed in the neoadjuvant setting. The 1- and 2-year recurrence-free survival rate was 100% and 92% for patients with any pathologic response, compared to 88% and 55% for patients who did not have a pathologic response ( P = 0.005). Increased immune cell infiltration at baseline, and decrease in M2 macrophages during treatment, were associated with pathologic response. Our results indicate that neoadjuvant relatlimab and nivolumab induces a high pCR rate. Safety during neoadjuvant therapy is favourable compared to other combination immunotherapy regimens. These data, in combination with the results of the RELATIVITY-047 trial 1 , provide further confirmation of the efficacy and safety of this new immunotherapy regimen. Patients with resectable clinical stage III or oligometastatic stage IV melanoma were given neoadjuvant relatlimab and nivolumab combination immunotherapy, which induced a high pathologic complete response rate, indicating the efficacy and safety of this regimen.